Decisão de Terminar o Rastreio do Cancro do Cólon e Reto: uma revisão sistemática - Joana Filipa Durão Janeiro Ferreira (2020)
Objectives: To review the literature about the decision to stop Colorectal Cancer (CRC) screening, concerning risks, benefits and patients and health care providers' opinions. Source of data: Search in the databases PubMed, Scopus and The Cochrane Library using the query: [screening AND cancer AND colorectal AND stop]. Methods: In order to do a systematic review without metanalysis, we included all original articles and studies based on microsimulation models about the decision to stop CRC screening. We included all results written in English or Portuguese, without publication year restrictions. To evaluate the quality of the articles, we used the ROBINS-I tool for observational and cross-sectional studies and the STRESS checklist for studies based on microsimulation models. Results: 231 results were identified, from which we selected six. We gathered three more articles obtained through additional search. Nine studies were included: six were related to the risks and benefits of screening; two were related to the patients' opinions; and one about health care providers' opinions. Our results showed that screening patients with more than 75 years old is only beneficial in two cases: when the patient have increased risk of CRC or when he is in good health status. This decision should be individualized. Furthermore, patients agree with an individualized decision and they appear to be more comfortable if this decision is shared with their health care provider. Concerning health care providers' opinions, the evidence is quite unclear and limited. Conclusions: There is very low evidence related to elderly patients and more studies are needed concerning the risk-benefit of CRC screening in these patients, stratified by age, comorbidities and CRC risk. We also need consolidation of the patients and health care providers' opinions in the decision. Key-words: Colorectal cancer, Screening, Elderly